Effects of taxpayer compliance with taxpayer consciousness as intervening variable - Lallo, Annas (Advances in Social Sciences Research Journal, 2019)
This study analyzes (1) the effect of tax authorities services on taxpayer awareness; (2) the effect of tax sanctions on taxpayer awareness; (3) the effect of tax audits on taxpayer awareness; (4) the effect of taxpayer awareness on mandatory compliance; (5) the effect of tax authorities services on taxpayer compliance; (6) the effect of sanctions on taxpayer compliance; (7) the effect of tax audits on taxpayer compliance; (8) the role of mediating the awareness of taxpayers in the influence of tax authorities services on taxpayer compliance; (9) the role of mediating the awareness of taxpayers in the effect of tax sanctions on taxpayer compliance; (10) the role of mediating taxpayer awareness in the effect of tax audits on taxpayer compliance. The population of this study is an individual taxpayer who performs free work registered at the North, South and West Makassar Primary Tax Office with 234.104 effective taxpayers still active. The research sample was 100 active taxpayers in the regional office of the directorate general of taxes in South Sulawesi. The sampling technique is purposive sampling. Data were analyzed using the Structural Equation Modeling method with the help of the Smart-PLS 3.0 program. The results of the study show that tax sanctions and tax audits have a direct or indirect effect on taxpayer compliance, while the services of tax authorities do not affect direct or indirect taxpayer compliance. The interesting result in this study is that the service of the tax authorities is not significant towards taxpayer compliance, but the positive influence fully mediates the effect of tax authority’s services on taxpayer compliance through taxpayer awareness.